2022
DOI: 10.1111/1755-0998.13627
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis: Water type and temperature affect environmental DNA decay

Abstract: Environmental DNA (eDNA) has been used in a variety of ecological studies and management applications. The rate at which eDNA decays has been widely studied but at present it is difficult to disentangle study‐specific effects from factors that universally affect eDNA degradation. To address this, a systematic review and meta‐analysis was conducted on aquatic eDNA studies. Analysis revealed eDNA decayed faster at higher temperatures and in marine environments (as opposed to freshwater). DNA type (mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 94 publications
0
29
0
Order By: Relevance
“…A range of abiotic environmental factors, biological conditions, and DNA characteristics have been shown to influence the eDNA degradation process. Among abiotic environmental factors, temperature is probably the most influential physical condition affecting eDNA decay rates (see Lamb et al, 2022 for a meta‐analysis). The literature consistently shows a markedly faster fish eDNA decay at higher water temperatures in various aquatic systems (Barnes et al, 2014; Jo et al, 2019; Nevers et al, 2018; Tsuji et al, 2017).…”
Section: Often Asked Questions About Edna‐based Surveysmentioning
confidence: 99%
See 2 more Smart Citations
“…A range of abiotic environmental factors, biological conditions, and DNA characteristics have been shown to influence the eDNA degradation process. Among abiotic environmental factors, temperature is probably the most influential physical condition affecting eDNA decay rates (see Lamb et al, 2022 for a meta‐analysis). The literature consistently shows a markedly faster fish eDNA decay at higher water temperatures in various aquatic systems (Barnes et al, 2014; Jo et al, 2019; Nevers et al, 2018; Tsuji et al, 2017).…”
Section: Often Asked Questions About Edna‐based Surveysmentioning
confidence: 99%
“…eDNA degradation rates exhibit a positive, linear correlation with temperature for Japanese eel (Kasai et al, 2020), mummichog ( Fundulus heteroclitus ; Andruszkiewicz et al, 2021), ayu sweetfish ( Plecoglossus altivelis altivelis ), and common carp (Tsuji et al, 2017), although the correlation slopes and intercepts differ substantially among studies. Also, Lamb et al (2022) showed that eDNA degrades more rapidly in marine than in freshwater environments, possibly due to a combination of abiotic and biotic conditions. Other environmental features, including water pH (Seymour et al, 2018; Strickler et al, 2015), dissolved oxygen (Weltz et al, 2017), and solar radiation (Strickler et al, 2015), have also been assessed for their effects on eDNA degradation, but the results are often less prominent than those for temperature.…”
Section: Often Asked Questions About Edna‐based Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Molecular Ecology Resources continues to publish comments, editorials, opinions, and technical review articles that provide guidance to authors on highly relevant topics. Several technical review articles were published last year that synthesize subject matter ranging from metabarcoding study design (Bohmann et al, 2022; Creedy et al, 2022; Lamb et al, 2022), to emerging model organisms (Wötzel et al, 2022), to guidance for experiments with blood‐born parasitic microbes (Rodríguez‐Pastor et al, 2022). Also, an Opinion article provided commentary on the need to appropriately select eDNA fractions in eDNA studies (Nagler et al, 2022).…”
Section: Top Content Published In Molecular Ecology Resourcesmentioning
confidence: 99%
“…The degradation rate of eDNA is hypothesized to be governed by several factors including extracellular nucleases secreted by microorganisms, which are themselves influenced by abiotic conditions like temperature, pH, and light irradiation (Barnes & Turner, 2016; Harrison et al, 2019; Lamb et al, 2022). The rate of degradation has recently been hypothesized to be influenced by the state of eDNA as well (Barnes & Turner, 2016; Harrison et al, 2019; Mauvisseau et al, 2022; Nagler et al, 2022).…”
Section: Introductionmentioning
confidence: 99%